Two Disputes of Methods, Three Constructivisms, and Three Liberalisms. Part I - Yefimov, Vladimir Maksovich (Economy of Regions, 2015)
The paper proposes to reconsider the methodology and history of economics radically, whether present day mainstream or heterodox versions of it. The profession of economists must definitely abandon Cartesian dualism and adopt Vygotskian constructivism. In fact constructivist economics already existed in the past and was cognitively very successful and socially very useful. It was the economics of Gustav Schmoller’s historico-ethical school and the institutionalist economics of John R. Commons, traditions of which are totally ignored by the contemporary community of economists. The former tradition was based on Dilthey’s hermeneutics and the latter on Peirce’s pragmatism. It is worth to underline that hermeneutics and pragmatism are both predecessors of Vygotskian constructivism. During the last two decades a lot was written by economists on pragmatist, constructivist and discursive approaches to the methodology and history of economics, but those who wrote on these topics viewed them from the dualistic point of view. My paper is an appeal to economists to reconsider Methodenstreit. The dispute of methods between Schmoller and Menger can be considered as a repetition of a similar dispute taking place more than two hundred years earlier between Robert Boyle and Thomas Hobbes. Schmoller-Menger dispute started soon after the beginning of the institutionalisation of experimentally-oriented economics which happened with the creation in 1873 of the Vereinfür Sozialpolitik. Boyle-Hobbes dispute started in 1660, when the Royal Society of London had been founded, the cradle of the institution of science. Schmoller was one of the creators of the Verein, and Boyle was one of the founders of the Royal Society. The activities of both societies were similar in several respects: they represented efforts to collect data, working out of detailed reports and collective evaluation of obtained results. For Hobbes, as for Menger, the model of ‘science’ was geometry. Boyle and Schmoller privileged collecting and analysing data. Boyle did win the dispute, Schmoller did loose. It happened because of different attitudes of powerful groups in societies towards natural scientific experimental research and experimental social research. They were interested in the former, and they saw much more danger than benefit for them in the latter. On the contrary, they were interested in abstract theoretical constructions justifying the market vision of society and laissez-faire. This kind of constructions corresponded to deeply enrooted scholastic traditions of European universities to teach theology and linked with it philosophy. In the framework of these traditions, mathematics was considered as a summit of the scientific approach. On the one hand, the adoption of constructivism by economists would turn their discipline into a science functionally close to natural sciences. On the other hand the Vygotskian constructivism, as a social and political philosophy, once accepted by economists, may lead them to become preachers of the communitarian liberalism with its emphasis on social responsibility, deliberative democracy, and discourse ethics.